"Double Critique" and the Sufi Praxis of Travel in Leila Ahmed's A Border Passage and Fatema Mernissi's Scheherazade Goes West. Issue 1 (1st June 2021) - Andrea, Bernadette
Abstract: This article focuses on two twentieth-century Anglophone Arab women writers' accounts of their travels to "the West": Leila Ahmed's A Border Passage: From Cairo to America—A Woman's Journey (1999), and Fatema Mernissi's Scheherazade Goes West: Different Cultures, Different Harems (2001). While their engagement with orientalist conceptions of the harem has received some attention, how and why they deploy Sufi texts, concepts, and cosmologies to advance their "double critique" of local and colonial patriarchies has not been subject to a sustained analysis, despite its salience in their travelogues. This article establishes that the Sufi praxis of travel ( safar ) becomes a facilitating framework, and ultimately a methodology derived from culturally grounded ways of knowing and being, for their overdetermined journeys toward what has been called "Islamic feminism."